Spatial organization of dinoflagellate genomes: Novel insights and remaining critical questions. Issue 6 (15th September 2021) - Lin, Senjie; Song, Bo; Morse, David
Abstract : As is true for many other aspects, genome architecture, evolution, and function in dinoflagellates are enigmatic and, in the meantime, continuous inspiration for scientific quests. Recent third‐generation sequencing and Hi‐C linkage analyses brought new insights into the spatial organization of symbiodiniacean genomes, revealing the topologically associated domains, discrete gene clusters and their cis and trans orientations, and relationships with transcription. Where do these new findings bring us in dinoflagellate genomics? Here, we aim to place these new results in the backdrop of the long history of research on this topic and in the context of what critical questions remain to be pursued in the future. The new data suggest, pending verification of other complete chromosome assemblies, a potential evolutionary trend in chromosome number decrease and length increase within the Symbiodiniaceae. While questions remain about the mechanics of the three‐dimensional chromosome structure and cell cycle‐related DNA replication, the mechanisms of gene transcription and genome size evolution, these latest findings set new starting points for further inquiries.